THE EFFECT OF THE KAMPUS MERDEKA (MBKM) POLICY ON ENGLISH PROFICIENCY AND GRADUATE EMPLOYABILITY: PENGARUH KEBIJAKAN KAMPUS MERDEKA (MBKM) TERHADAP KECAKAPAN BAHASA INGGRIS DAN KEMAMPUAN KERJA LULUSAN - Stevani, Margaret; Yanti, Novi; Mahfud Hidayat, Ikhwan (LPPM UPMI, 2024)
The Kampus Merdeka (MBKM) policy, introduced by the Indonesian government in 2020 under Regulation No. 3/2020, aimed to address the mismatch between graduate job readiness and industry demands by enhancing both technical and personal competencies among students. This research evaluated the impact of the MBKM policy on English proficiency and graduate employability at Universitas Pembinaan Masyarakat Indonesia, using a sample of 16 students from the English Education Program. The mixed-methods research included a quantitative survey, qualitative interviews, and observation data. Findings indicated that the MBKM policy significantly improved English proficiency and employability by integrating transferable skills into curricula, providing work experience, and incorporating real-world English usage. Students reported enhanced communication, public speaking, argumentation, teamwork, problem-solving, and information management skills. The research concluded that the MBKM policy effectively bridged the gap between language education and employability, highlighting the essential role of English education in preparing graduates for career success and long-term professional development.